The role of the cannabinoid receptor in adolescents′ processing of facial expressions - Ewald, Miriam-Anais; Banaschewski, Tobias; Poustka, Luise; Flor, Herta (European journal of neuroscience, 2016)
The processing of emotional faces is an important prerequisite for adequate social interactions in daily life, and might thus specifically be altered in adolescence, a period marked by significant changes in social emotional processing. Previous research has shown that the cannabinoid receptor CB1R is associated with longer gaze duration and increased brain responses in the striatum to happy faces in adults, yet, for adolescents, it is not clear whether an association between CBR1 and face processing exists. In the present study we investigated genetic effects of the two CB1R polymorphisms, rs1049353 and rs806377, on the processing of emotional faces in healthy adolescents. They participated in functional magnetic resonance imaging during a Faces Task, watching blocks of video clips with angry and neutral facial expressions, and completed a Morphed Faces Task in the laboratory where they looked at different facial expressions that switched from anger to fear or sadness or from happiness to fear or sadness, and labelled them according to these four emotional expressions. A-allele versus GG-carriers in rs1049353 displayed earlier recognition of facial expressions changing from anger to sadness or fear, but not for expressions changing from happiness to sadness or fear, and higher brain responses to angry, but not neutral, faces in the amygdala and insula. For rs806377 no significant effects emerged. This suggests that rs1049353 is involved in the processing of negative facial expressions with relation to anger in adolescence. These findings add to our understanding of social emotion-related mechanisms in this life period.
Gesehen am 10.01.2019
First published: 03 November 2015